PERLINDUNGAN HUKUM BAGI KONSUMEN BANK DALAM UNDANG-UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN (OJK) - Marsitiningsih, Marsitiningsih (Solusi, 2018)
The legal relationship between the bank and the customer exists because of the depositary agreement. The law creates rights and obligations. Business activities carried out by banks authority so greater the supervision. To overcome this, then the arrangement and other financial institutions so one becomes the financial services authority (OJK) in Law number 21 of 2011. There are two different functions in one bank institution of Indonesia Bank that is regulation and supervision function, fuction of monetary authority, so the bank Indonesia prioritizes monetary policy instruments rather than strengthening the regulatory and supervisory fuctions. Bank supervision in the financial services authority is supervision on the health of banks, determination of bank status and prudential principles. The right of customers to get protection of their rights, especially customer education and dispute resolution. Law number 21 of 2011 regulates OJK authorized to undertake consumer and community harm prevention measures, perform customer complaint services and safeguard measures by defending and fiing a lawsuit to obtain a change